Identification of Complex Fluid Properties in Condensate Gas Reservoirs Based on Gas–Oil Ratio Parameters Calculated by Optimization Mathematical Model - Zhao, Bin; Li, Zhaoping; Gao, Chuqiao; Tang, Yang (Frontiers in Energy Research, 2022)
In the production development stages of volatile oil reservoirs and condensate gas reservoirs, especially in the early stages of production, the phenomenon of high gas-oil ratio often occurs. As a result, the prediction results of oil and gas are greatly deviated from the actual situation, which seriously affects the implementation of potential excavation and increase production operation for condensate reservoirs. Therefore, accurate identification of condensate gas, volatile oil and conventional light oil is a key issue to improve the development efficiency in condensate reservoirs. However, due to the similar response characteristics of geophysical logging and gas logging for condensate gas, volatile oil and light oil reservoirs, the qualitative identification effect based on conventional logging and gas logging information is not ideal. Therefore, we propose a method to calculate gas-oil ratio by introducing gas logging information and use the gas-oil ratio quantitative calculation results to identify condensate gas, volatile oil and light oil. First, we establish a physical model of the formation components of the condensate gas reservoir. Based on this physical model, we establish the response equations of various logging tools, and evaluate the correlation between the gas logging information and the production gas-oil ratio to establish the response equation of gas logging. Then, we comprehensively use the well logging and gas logging response equations to establish an optimization mathematical model, solve the optimization objective function, obtain the relative content of natural gas and movable oil in the formation to calculate the gas-oil ratio parameters, and finally use this calculation result of the gas-oil ratio quantitatively evaluates the fluid type. The application results show that the gas-oil ratio quantitative calculation method we proposed can calculate the gas-oil ratio parameter accurately, and the calculation results are consistent with the formation testing data, which provides technical support for the identification of complex fluid properties in condensed gas reservoirs.